Integrasi Keterampilan Berpikir Tingkat Rendah (LOTS) dan Tinggi (HOTS) dalam Pembelajaran Pendidikan Agama Kristen - Marthen Mau (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Christian religious education (Christian Religious Education) teaching still lacks the capacity to facilitate students' development of LOTS and HOTS. Therefore, students need to be actively involved in the learning process. Students are unable to complete difficult-level questions due to their low-level thinking skills, but they still tend to complete lower-level questions. This study aims to integrate low-level and high-level thinking skills into the Christian Religious Education (Christian Religious Education) learning process. Using qualitative research with a library approach, the results revealed students' ability to understand Christian Religious Education material through the integration of low-level (LOTS) and high-level (HOTS) thinking skills. The study concluded that LOTS and HOTS can be integrated into Christian Religious Education (Christian Religious Education) learning, enabling students to answer both easy and difficult questions when given by educators in classroom assessments and solve problems encountered in real life. Therefore, Christian religious education needs to focus on developing these two thinking skills in order to improve the overall quality of learning.